Effects of Adhesives on Quality Biomass Briquette - Abdurrouf Abdurrouf; Istiroyah Istiroyah; Gancang Saroja (Natural B, Journal of Health and Environmental Sciences, 2011)
Production of briquettes from organic waste with starch as an adhesive, has been done. The briquette's quality is improved by (i)  the milling of organic waste is conducted in dry phase, and (ii) the mixing between organic waste and starch as an adhesive is carried out on raw phase. This study shows that the best briquette was obtained when the ratio of organic wastes - starch was 10:3. In such composition, mass of the produced briquette was more than 50% of the mass of organic waste. For more improvement, it is necessary to find a better pressing and drying technique. It is also need to make briquette in large numbers to improve its characterization.